The role of the State in the public provision of care: new strategies and impacts on women workers in the sector. Basque Autonomous Community’s case. - Zalbidea López, Garazi (Papeles de Europa, 2023)
Basque Autonomous Community’s care system has turned overwhelmed with the outbreak of the pandemic, reflecting the exhaustion of a Social Services model which is increasingly abandoned by public administrations. Moreover, it has shown the risks this implies for sector’s workers, users, and the population as a whole. With the aim of deepening in the dismantling process of public care system, the following study aims to analyze the main dynamics in the reconfiguration of public strategy in this regard, as well as its impact on sector’s working conditions. In order to carry out the research, an own methodology based on social care model has been developed. Results show that carried out strategies, involving the slowing down of public spending, the privatization of services, and the prioritization of cash transfers are impacting negatively on jobs’ quality. It is thus confirmed that the withdrawal of Basque Government in relation to care contributes to its devaluation, as well as to the precariousness of women who carry these works out.
Keywords: Public care system; State's role; privatization; women workers; precariousness